Strategi Komunikasi dalam Pengambilan Keputusan Kepemimpinan Kolektif pada Pencalonan Pilkada Kupang 2017 (Jurnal Kajian Media, 2018)
The General Election Commission (KPU) is a national, permanent and independent election management department. The working area of the KPU covers the whole of Indonesia consisting of KPU, Provincial KPU, Regency KPU, PPK, PPS, KPPS. Kupang Municipal Election Commission is a part of KPU institution which organizes general election at city level including holding election of Mayor and Vice Mayor. Judging from the aspect of leadership, the leadership model of KPU is collective because decision making is done together. Group decision makers have advantages over individuals because there is a process of interaction between group members. In this paper using two theories of decision theory and functional Theory. The objectives of this research are: (1) to know the procedure of plenary meeting of nomination stage, and (2) to know the dynamics of decision making in discussing, analyzing and formulating the decision of nomination stage in Kupang Mayor and Vice Mayor election in 2017. This research is a qualitative research with informants consisting of chairmen and members of the KPU and the secretariat of KPU Kupang City. Keywords: Leadership, decision making, group dynamics and collective decision making